The bacterial rhizobiome of hyperaccumulators: future perspectives based on omics analysis and advanced microscopy - Visioli, Giovanna; D'Egidio, Sara; Sanangelantoni, Anna M. (Frontiers in Plant Science, 2015)
Hyperaccumulators are plants that can extract heavy metal ions from the soil and translocate those ions to the shoots, where they are sequestered and detoxified. Hyperaccumulation depends not only on the availability of mobilized metal ions in the soil, but also on the enhanced activity of metal transporters and metal chelators which may be provided by the plant or its associated microbes. The rhizobiome is captured by plant root exudates from the complex microbial community in the soil, and may colonize the root surface or infiltrate the root cortex. This community can increase the root surface area by inducing hairy root proliferation. It may also increase the solubility of metals in the rhizosphere and promote the uptake of soluble metals by the plant. The bacterial rhizobiome, a subset of specialized microorganisms that colonize the plant rhizosphere and endosphere, makes an important contribution to the hyperaccumulator phenotype. In this review, we discuss classic and more recent tools that are used to study the interactions between hyperaccumulators and the bacterial rhizobiome, and consider future perspectives based on the use of omics analysis and microscopy to study plant metabolism in the context of metal accumulation. Recent data suggest that metal-resistant bacteria isolated from the hyperaccumulator rhizosphere and endosphere could be useful in applications such as phytoextraction and phytoremediation, although more research is required to determine whether such properties can be transferred successfully to non-accumulator species.